Art of the Roman Empire AD 100-450 Imperial Rome and Christian triumph - Elsner, Jas (Oxford Oxford University Press, 2018)
"The passage from Imperial Rome to the era of late antiquity, when the Roman Empire underwent a religious conversion to Christianity, saw some of the most significant and innovative developments in Western culture. This stimulating book investigates the role of the visual arts, the great diversity of paintings, statues, luxury arts, and masonry, as both reflections and agents of those changes. Elsner's ground-breaking account discusses both Roman and early Christian art in relation to such issues as power, death, society, acculturation, and religion. By examining questions of reception, viewing, and the culture of spectacle alongside the more traditional art-historical themes of imperial patronage and stylistic change, he presents a fresh and challenging interpretation of an extraordinarily rich cultural crucible in which many fundamental developments of later European art had their origins. This second edition includes a new discussion of the Eurasian context of Roman art, an updated bibliography, and new, full colour illustrations."--
Part I: Images and power. A visual culture ; Art and imperial power -- Part II: Images and society. Art and social life ; Centre and periphery ; Art and death -- Part III: Images and transformation. Art and the past: antiquarian eclecticism ; Art and religion ; The Eurasian context -- Part IV: Epilogue. Art and culture: cost, value, and the discourse of art -- Afterword: Some futures of Christian art.
First edition published 1998 by Oxford University Press with the title: Imperial Rome and Christian triumph : the art of the Roman Empire AD 100-450.
Includes bibliographical references (pages 263-267, 285-295) and index.
Keywords: 30 B.C.-284 A.D; Art, Roman; Art, Early Christian; Art, Early Christian; Art, Roman; Rome -- History -- Empire, 30 B.C.-284 A.D; Rome (Empire); History